Professional Development of Teachers in the Tshwane District for Effective Environmental Education - Johanna G. Ferreira; Johannah Bopape (Environmental Association of Southern Africa, 2009)
Many teachers in South Africa may have had little exposure to environmental education, yet the revised National Curriculum Statement emphasises the infusion of environmental education into all learning areas. The question arises whether professional development of teachers in environmental education is required for effective teaching in this field. The main aim of this study was to ascertain whether teachers have acquired the knowledge and skills necessary to infuse environmental education in all learning areas. Besides a literature review of sources, a questionnaire was developed as a research tool and 163 teachers in the Tshwane North District Office were involved in the survey. The results suggest that environmental education will have to be addressed in the professional development of teachers to ensure effective implementation of the National Curriculum Statement.